Dinamika Konflik Orang Tua dan Regulasi Emosi Anak: Pendekatan Mawdhu’i atas Hadits tentang Keluarga Sakinah dan Rahmah - Syifa Firahmatika; Ahmad Ridla Syahida (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This article maps and interprets hadiths on sakinah and rahmah as an ethical framework for understanding interparental conflict and its implications for children’s emotion regulation. The study is urgent because poorly managed marital conflict can undermine children’s emotional security, heighten hypervigilance, and weaken self-soothing, thereby disrupting socio-emotional development. Its contribution lies in integrating thematically selected hadiths from diverse authoritative sources with developmental and learning psychology, focusing on emotional security, emotion socialization, behavioral modeling, and responsive parenting as protective factors. The discussion outlines the meanings of sakinah and rahmah and offers a tarbawi analysis of key hadiths on tranquility and mercy, compassion, rifq in communication, anger control, avoidance of harm, and the importance of iṣlāḥ (reconciliation). The synthesis connects these moral teachings with psychological mechanisms and educational implications to support families and schools in cultivating a secure, warm emotional climate for children